Synthesis of Hierarchically Ordered Porous Silica Materials for CO2 Capture: The Role of Pore Structure and Functionalized Amine - Xiaoqi Jin; Jinlong Ge; Liyuan Zhang; Zhong Wu; Linlin Zhu; Mingwen Xiong (Inorganics, 2022)
Hierarchically ordered porous silica materials (HSMs) with a micro/mesoporous structure were successfully prepared with the sol-gel method using dextran, dextran/CTAB, and CTAB as templates. The obtained hierarchically structured silica was successfully modified with amine groups through post-grafting and one-pot methods. Their architectural features and texture parameters were characterized by XRD, N2 adsorption–desorption isotherms, SEM, TEM, FTIR, and TGA techniques. The results demonstrated that the pore structure depended on the reaction temperature and the amount of CTAB added in the synthesis procedure. A series of porous silica with hierarchical pore structures possessed abundant micropores, ordered mesopores, and a tunable surface area and pore volume. After modification, the ordered structure of the hierarchical porous silica almost disappeared due to the presence of amine groups in the pore channel. Furthermore, to explore the effect of pore structures and amine groups on CO2 adsorption performance, before and after amine modification of HSMs, adsorbents were evaluated regarding the capacity of collecting CO2 for comparison. According to these results, the varying microporous content, pore size distribution, and density of the amine groups were important factors determining the capacity of CO2 capture.